2007
DOI: 10.1143/jjap.46.3296
|View full text |Cite
|
Sign up to set email alerts
|

Surface Passivation of Crystalline and Polycrystalline Silicon Using Hydrogenated Amorphous Silicon Oxide Film

Abstract: Excellent passivation properties of hydrogenated amorphous silicon oxide (a-SiOx:H) prepared by very high frequency plasma-enhanced chemical vapor deposition (VHF PECVD) at a low substrate temperature (170 °C) on crystalline and polycrystalline silicon (Si) wafers are reported. Films were characterized by ellipsometry, Fourier transform infrared spectroscopy (FTIR), ultraviolet–visible (UV–vis) spectrophotometry, and dark-conductivity and photoconductivity measurements. A comparison of the results with those f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 12 publications
0
31
2
Order By: Relevance
“…5 shows the variation of C −2 with V for the solar cells with and without a p-nc-Si:H buffer layer deduced from the C-V measurements at 1 MHz. The frequency of 1 MHz is the same as that adopted by several workers to investigate the hydrogenated amorphous silicon materials using the C-V characteristics [19][20][21]. In Fig.…”
Section: Influence Of P-nc-si:h Buffer Layer On Cell Performancementioning
confidence: 99%
“…5 shows the variation of C −2 with V for the solar cells with and without a p-nc-Si:H buffer layer deduced from the C-V measurements at 1 MHz. The frequency of 1 MHz is the same as that adopted by several workers to investigate the hydrogenated amorphous silicon materials using the C-V characteristics [19][20][21]. In Fig.…”
Section: Influence Of P-nc-si:h Buffer Layer On Cell Performancementioning
confidence: 99%
“…Such a scenario is also probable since several studies have demonstrated that, in addition to field effect passivation, silicon dielectric layers with relatively high hydrogen content chemically passivate silicon via hydrogen release during a subsequent heating step. 31,44 Comparing the chemical bond densities in Tables 6 and 8 with the V oc and J sc values in Tables 7 and 9, respectively, gives a global relationship between the chemical bonding of the passivating layer and the performance of the test cells. Without HPP, increasing [Si−H] in the passivating layer increased both J sc and V oc , in agreement with reports for multicrystalline silicon.…”
Section: Discussionmentioning
confidence: 99%
“…The passivation of semiconductor surfaces is important to achieve a long lifetime of photo-induced minority carriers, which is required for fabricating high-performance photosensors and photovoltaic devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Many famous passivation techniques have been developed for surface passivation, for example, formation of thermally grown SiO 2 layers [20], hydrogenation treatment [21,22], fieldeffect passivation caused by fixed charges in SiN or aluminum oxide [23,24], and high-pressure H 2 O vapor heat treatment [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%